Determinantes do acesso às transferências voluntárias: análise dos municípios brasileiros entre 2008 e 2016 - Silva, Valquíria Souto da (2019)
The intergovernmental transfers are contained in a system of rules that organize the responsabilities on the collection and the provision of public goods, denominated Fiscal Federalism. In Brazil, tax competencies are mostly concentrated in the federal government, with intergovernmental transfers taking on a role of reallocating resources in states and municipalities, since the distribution of resources between the entities is heterogeneous. From this context, the objective was to analyze the factors that determined the access to the voluntary transfers of the Federal Union, from 2008 to 2016. For this, the panel regression method was used from the definition of Technical, Political and Redistributive Factors in access to resources of voluntary nature. For the Technical, although a large number of municipalities have participated in the process, the fact of presenting a proposal to become a subscriptor did not show to be a relevant item to achieve better performance; still, part of the state capacity indicators demonstrated that the autonomy and professionalization of bureaucracy negatively influenced the funding process. In the Politician, the occurrence of presidential elections positively influences the volume of resources transferred to the municipalities while the holding of local elections negatively impacted the decentralization of these resources, which may be an indication that in years where local governments either end their mandates or are working for their reelections, subscription process is reduced. And, regarding the Redistributive, the voluntary transfers behaved as a distributive and not a redistributive policy, since the results point to the prioritization of municipalities with lower rates of human development or that have low municipal self-revenue rates.